OBTURATOR FABRICATION WITH MAGNET ATTACHMENT - Lita Rosa, Mia Laksmi (Journal of Vocational Health Studies, 2019)
Background: Development of science and technology led to people having birth defects (congenital), trauma or because of there sected tumor can be made of a prosthesis. Purpose: To learn the technique of making obturator with magnet attachment. Review: Assembly of magnet in obturator can improve the stability and retention of the prosthesis. Conclusion: The techniques of making obturator with magnetic attachment begins with making the double impression. The part defect is waxed on a master cast, and the contoured wax lid was fabricated on the master cast to close the hollow obturator. The lid along with the magnetic assembly was attached to the obturator with auto polymerizing resin. Obturator is inserted in the patient and created a master cast for the fabrication of denture. Wax of master cast of denture is assembled magnet for attachment to the obturator, then flasking, wax boil-out of master cast, acrylic processing, deflasking, finishing, and polishing.